Community Perceptions on Health and Environmental Implications of Poor Management of Solid Waste Materials around local Dump Sites in the Buea Municipality, Cameroon (American Journal of Education and Technology, 2023)
Numerous urban areas are today faced with many challenges posed by poor waste management and disposal especially in the developing countries. Analogously, these challenges are faced by urban dwellers in the Buea Municipality. The study aims at assessing the health and environmental implications of poor waste management in the Buea Municipality. It is an observatory and interrogatory study with a cross-sectional research design and dealing with 250 household dwellers selected through the simple random sampling technique. Primary data were obtained through questionnaires, interview guides, and field observations, supplemented with secondary data from magazines and published articles. Data collected were added codes and themes and inputted on Excel Version 17 and SPSS Version 13. Descriptive and inferential statistical techniques were adopted to establish percentiles, frequencies and magnitudes. Findings revealed that the siege population in the Buea municipality lacks adequate waste management facilities and this has pushed a significant proportion of them to always dump their waste materials generated from their booming domestic and economic activities into drainage channels, roadsides, and pits. The poor management of these waste materials has resulted to the occurrence of water and airborne diseases such as diarrhea, dysentery, cholera and typhoid fever affecting the population. Portable water sources and homes are also polluted by effluence from these waste dump sites. Urban dwellers adapt by boiling water from contaminated sources and cleaning up of nearby dirty gutters but their efforts are unfruitful. The work concludes that the Buea Municipality offers perennial and inter-generational opportunities to its population and recommends that holistic and bottom-top approaches such as daily clean-up campaigns; provision of trash-cans as well as the sensitization of the general community must be implemented in order to provide a congenial environment for the population.